2021
DOI: 10.2196/25969
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Interventions to Support Prescription Opioid Tapering in Patients With Chronic Pain: Qualitative Study of Patients’ Perspectives

Abstract: Background Patients with chronic pain who are tapering prescription opioids report a need for greater support for coping with symptoms of pain and withdrawal. Mobile health (mHealth) technologies (SMS text messaging– or app-based) have the potential to provide patients with educational, emotional, and motivational support for opioid tapering beyond what is offered by their health care provider. However, it is not known whether patients with chronic pain who are tapering opioids would be willing or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 44 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…This pilot trial and development of the mHealth intervention was in response to research indicating that patients with chronic pain who are tapering opioid medications have a need and desire for support above and beyond that provided by their healthcare providers (ie, ‘out of office hours’). 28 34 The initial mHealth intervention prototype and trial design (procedures and measures) were developed in close collaboration with clinician-researchers with expertise in pain management and opioid tapering (AS, MF and BD) and a consumer representative (LD). The initial intervention design was then revised in response to feedback from panels of consumers and clinical experts (see Section 2.5.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This pilot trial and development of the mHealth intervention was in response to research indicating that patients with chronic pain who are tapering opioid medications have a need and desire for support above and beyond that provided by their healthcare providers (ie, ‘out of office hours’). 28 34 The initial mHealth intervention prototype and trial design (procedures and measures) were developed in close collaboration with clinician-researchers with expertise in pain management and opioid tapering (AS, MF and BD) and a consumer representative (LD). The initial intervention design was then revised in response to feedback from panels of consumers and clinical experts (see Section 2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Second, participants indicated that the content of text messages should be familiar, acting as a reminder of helpful concepts and coping strategies rather than being the primary source of information. 28 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations